SÍNTESE E CARACTERIZAÇÃO DO SISTEMA ESPINÉLIOS CO1-XCUXFE2O4 (X = 1,0, 0,75,0,50, 0,25, 0,0) PELO MÉTODO DOS PRECURSORES POLIMÉRICOS - Silva, Maya Dayana Penha da (2012)
Ferrites are complex oxides, thermally stable, that presents crystalline structures equivalent to the spinel mineral.These solids alsoretain significant dielectric, magneticand catalytic properties. Thus, this work aims to obtain Co1-xCuxFe2O4spinel nanoparticles (x = 0.00, 0.25, 0.50, 0.75, 1.00) by the polymeric precursor method as well as evaluates the effect of its thermal treatment (700 - 1200 °C) over the crystalline structure. Therefore, all spinel structures were characterized by means of Raman and infrared vibrational spectroscopies and X-ray powder diffraction (XRPD). According to the X-ray diffraction patters, all the primary CoFe2O4 adopts an ideal inverse spinel structure [(Fd3 ̅m (O_h^7))], whereas the CuFe2O4 materials preferentially assume tetragonal distorted spinel structure [(I41/amd(D_4h^19))], except the 700 and 800 oC annealed CuFe2O4, that was indeed hematite. Besides, such case the FWHM analysis has indicates that the ternary thermal treatment leads to a higher organization of the lattice, as well as, increases the crystallite sizes. In general, the average crystallite sizes for CuFe2O4 varies between 27 35 nm; whereas, for the CoFe2O4 and Co-substituted CuF2O4 are respectively 28 37 nm and 33.3 52.6 nm. The crystal microdeformation oscillates between 0.17 and 0.32%, reducing, in most cases, with the thermal evolution. Raman spectra for CuFe2O4 samples shows vibrational modes at about 166 (F2g), 456 (F2g), 519 (F2g), 217 (Eg), e 686(A1g) cm-1. In other hand, CoFe2O4 samples present vibrational modes at 195, 457 and 587 cm-1 (all F2g symmetries), 298 cm-1 (A1g) and 671 cm-1(Eg). Similar optical-active modes were detected for the Co-substituted ferrites. Conversely, FTIR spectra for all CuFe2O4 shows characteristic stretching at about 531.79 559.45 cm-1 (Fe-O)A, 605.18 672.12 cm-1 (Cu-O)Aand 474.69 397.33 cm-1 (Fe-O)B. However, the CoFe2O4 samples exhibits strong stretching modes at 581.70 578.51 cm-1 (Co-O)A. Similar modes were also observed for the intermediary ferrites. Finally, the UV-vis spectra for CuFe2O4 shows 6A1g → 4Eg (G) (Fe3+ )B, and 6A1g → 4Eg (G) (Cu2+)Atransitions between 2.14 2.72 eV and 1.76 1.80 eV, respectively. However, the CoFe2O4 ferrites presents6A_1g → 2A_2g(P)(Co2+)A electronic transitions 2.11 and 2.39 eV.